Do the Dento-Thalamic Connections of Genetic Absence Epilepsy Rats from Strasbourg Differ from Those of Control Wistar Rats? - (:unkn) unknown (MARY ANN LIEBERT, INC, 2019)
The thalamo-cortical circuit is important in the genesis of absence epilepsy. This circuit can be influenced by connecting pathways from various parts of central nervous system. The aim of the present study is to define the dento-thalamic connections in Wistar animals and compare the results with genetic absence epilepsy rats from Strasbourg (GAERS) using the biotinylated dextran amine (BDA) tracer. We injected BDA into the dentate nucleus of 13 (n=6 Wistar and n=7 GAERS) animals. The dento-thalamic connections in the Wistar animals were denser and were connected to a wider range of thalamic nuclei compared with GAERS. The dentate nucleus was bilaterally connected to the central (central medial [CM], paracentral [PC]), ventral (ventral medial [VM], ventral lateral [VL], and ventral posterior lateral [VPL]), and posterior (Po) thalamic nuclei in Wistar animals. The majority of these connections were dense contralaterally and scarce ipsilaterally. Contralateral connections were present with the parafascicular (PF), ventral posterior medial, ventral anterior (VA), and central lateral (CL) thalamic nuclei in Wistar animals. Whereas in GAERS, bilateral connections were observed with the VL and CM. Contralateral connections were present with the PC, VM, VA, and PF thalamic nuclei in GAERS. The CL, VPL, and Po thalamic nucleus connections were not observed in GAERS. The present study showed weak/deficit dento-thalamic connections in GAERS compared with control Wistar animals. The scarce information flow from the dentate nucleus to thalamus in GAERS may have a deficient modulatory role on the thalamus and thus may affect modulation of the thalamo-cortical circuit.
Keywords: BDA; connections; dentate nucleus; GAERS; thalamic nuclei; WHITE-MATTER INTEGRITY; CEREBELLAR OUTPUT; GENERALIZED SPIKE; FUNCTIONAL CONNECTIVITY; BASAL GANGLIA; FRONTAL-LOBE; NUCLEUS; PROJECTIONS; NETWORK; MOTOR